Analysis of Violations of the Principle of Language Politeness in The Sultan Entertainment Talk Show Program on SCTV - Octa Ulandari; Intan Sari Ramdhani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to describe the observance of the principle of language politeness in the speech of the host of The Sultan talk show on SCTV, and to describe the violation of the principle of language politeness in the host's speech to guest stars in the talk show program The Sultan Entertainment on SCTV. This research approach is qualitative. The design of this study is a qualitative description. This research produced description data in the form of sentences of the principle of language politeness on talk shows. Data analysis in this study includes data identification, data presentation, and drawing conclusions. On data identification, sentences are classified according to the categories that appear on the principle of politeness. Data analysis techniques are carried out by presenting data, and drawing conclusions. This research data collection technique uses the listening method with the note taking technique. This method has advanced techniques, namely the proficient listening technique, the proficient free listening technique, and the note-taking technique. The research steps that are the instruments are the researchers themselves. The result of the study was a form of violation of language politeness on the talk show The Sultan Entertainment on SCTV.